Molecular characterization of Malaimadu cattle - KARTHICKEYAN, S M K; KUMARASAMY, P; CHANDRA, A ROSALYN MARY; HEPSIBHA, P; SIVASELVAM, S N (The Indian Journal of Animal Sciences, 2019)
Malaimadu cattle, a draught cattle found in villages adjoining Western Ghats of Tamil Nadu, is known for their workability. The population has possessed high number of allelic variability with few alleles at low frequencies and was non-bottlenecked proving no recent reduction in effective population size. This study revealed that Malaimadu cattle possess high within-breed genetic diversity with many polymorphic loci and hence could be recognised as a separate breed.